Implementation of cell-to-cell routing scheme in a large scale conceptual hydrological model. (March 2018) - Paul, Pranesh Kumar; Kumari, Nikul; Panigrahi, Niranjan; Mishra, Ashok; Singh, Rajendra
Abstract: A cell-to-cell routing (ROU) module has been implemented in a large-scale conceptual hydrological model, developed for the entire landmass of India with a 5 km × 5 km grid cell resolution. The ROU module is based on the principle of time variant spatially distributed direct hydrograph (SDDH) travel time method to route streamflow to the catchment outlet. The integrated model has been calibrated and validated at the Kabini dam flow measurement site over 2001–2006 and 2007–2010, respectively. Nash Sutcliffe Efficiency (NSE) is found to be 0.55 and 0.47 for the calibration and the validation period, respectively. The obtained NSE value shows that the model is satisfactorily calibrated and ROU module compliments the other modules. The comparison between model simulation results with implemented and original routing schemes show that implemented method, with modified parameterization, outperforms the original one. The overall results support the applicability of the implemented routing scheme. Highlights: A cell-to-cell routing (ROU) module has been implemented in a large-scale conceptual hydrological model. It is based on the principle of time variant spatially distributed direct hydrograph (SDDH) travel time method, with modified parameterization. The integrated model has been calibrated and validated for streamflow at Kabini dam flow measurement site. The overall results support the applicability of the implemented cell-to-cell routing scheme in the large-scale conceptual hydrological model with grid cell resolution of 5 km × 5 km.